Genotypic variability in isolates of Rhizoctonia solani from rice, maize and greengram - PRADEEP KUMAR SINGH, JYOTILEKHA BORAH and S.N. RAI, PANKAJ KUMAR MISHRA, ROBIN GOGOI* (Indian Phytopathology, 2015)
Molecular characterization of Rhizoctonia solani (Kühn) isolates of three hosts, viz.rice, maize and greengram was done using three molecular markers, viz. Random Amplified Polymorphic DNA (RAPD), Universal Rice Primer (URP) and Internal Transcribed Spacer Region (ITS). The RAPD markers were found suitable for resolving the genetic polymorphism hidden among 22 R. solani isolates. The phylogenetic analysis based on RAPD revealed three clusters comprising two major clusters of maize and rice, and one minor cluster with four outliers of the isolates. The two greengram isolates, PRS21 and PRS22, were clustered with maize isolates. The URP markers could not identify and clearly differentiate the isolates of R. solani. Although these markers could sparsely cluster rice and maize isolates separately into two major clusters but most of the isolates were not clearly placed in any of these clusters. Both greengram isolates clustered together with maize which was analogous to RAPD results. The cluster analysis of full length ITS region formed four groups without any clear cut differentiation among isolates and did not follow the pattern of RAPD and URP analyses.